Growth and Yield Models for Plantation-Grown Cupressus lusitanica for Central Kenya - Kuria , Charles N.; Kirongo, Balozi B.; Kipkore , Wilson (African Journal of Education,Science and Technology (AJEST), 2019)
The demand for timber in Kenya is increasing. However, forest managers do not have an effective tool for estimating the growth and yield of the resource against the demand to enable sustainable management. In this study, a method for estimating growth and yield of Cupressus lusitanica plantations in Central Kenya based on a statistical model that directly relates volume to other parameters such as diameter and total height is considered. The study developed a set of growth models based on height against age, height against diameter at breast height (dbh) as well as the dhb against age. Tree height and age showed exponential relationship of the form Ht = b*Age^c, while the height and dbh was developed using models of the form Ht = a + b(dbh)^c and dbh was related to the age by equation of the form dbh = a*(Age)^b. The relationship between volume and dbh and height was fully fitted with third order differential equation of cubic function. At dbh lower than 0.2 m the volume increased at slower rate, followed by an exponential increase in volume between dbh 0.2 to 0.45m and then a plateau thereafter. Using diameter at breast height and height, the volume equation was developed as; V = -0.1247+ 0.02233*dbh2-0.0233*H+ 0.0012*H2, which showed higher model fit to volume than the model currently in use, with the latter overestimating volumes at extreme high or low values but underestimated most intermediate volumes. The developed models are recommended for integration into forest information systems for Cypress plantations management in Central Kenya